2021
DOI: 10.4236/ojer.2021.102003
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Correlation between High Frequency Geomagnetic Variations and Seismicity in the Caribbean

Abstract: An analysis between the hourly distribution of earthquakes in three areas of the Caribbean and the high-frequency variations of the geomagnetic field is presented. The number of earthquakes selected for each zone is between 10,000 and 43,000, which guarantees a statistically significant distribution. The hourly distributions of seismicity in all areas show a bay-shape distribution with a significant increase in the number of earthquakes at night, from 11 PM to 5 AM. For example, in eastern Cuba 36.7% of earthq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…It clearly demonstrates the effect of the Sun on the earthquake activity: solar activity stimulates seismic activity triggering earthquake focuses. Open Journal of Earthquake Research The hourly distribution of earthquakes in the Caribbean area was revealed to exhibit significant correlation with the distribution of high-frequency geomagnetic variations; the latter were recorded by the GOES13 satellite and by SJG ground magnetic station [40]. The hourly distribution of seismicity has a bay-shape form with a significant increase in the number of earthquakes at night, from 11 PM to 5 AM.…”
Section: Magnetically Controlled Seismicitymentioning
confidence: 94%
“…It clearly demonstrates the effect of the Sun on the earthquake activity: solar activity stimulates seismic activity triggering earthquake focuses. Open Journal of Earthquake Research The hourly distribution of earthquakes in the Caribbean area was revealed to exhibit significant correlation with the distribution of high-frequency geomagnetic variations; the latter were recorded by the GOES13 satellite and by SJG ground magnetic station [40]. The hourly distribution of seismicity has a bay-shape form with a significant increase in the number of earthquakes at night, from 11 PM to 5 AM.…”
Section: Magnetically Controlled Seismicitymentioning
confidence: 94%